SUSE linux enterprise server security (cource 3075) : SLES to VMWere server student manual (PDF) self-study wookbook (PDF) self study files - 354662 Eckert, Jason W.; Novell, Inc. (Australia ; Boston : Thomson Course Technology, 2008)
57